Odškodninska odgovornost v zvezi s postopki javnega naročanja - Možina, Damjan (Podjetje in delo, 2018)
The paper discusses the issues of liability for damage due to breaches in public procurement procedures. Firstly, the situation in EU law is presented, based primarily on the so-called general remedies directive (89/665/EEC), which guarantees recovery of damage only on a very general level, whereas the details are left to the law of the member states. The "utilities" remedies directive (92/13/EEC) contains a more detailed regulation of one aspect of damages (recovery of cost of preparing a bid). The paper is focused on the analysis of Slovenian law. It starts with a discussion of possibilities as to the legal basis of damages claims, which is followed by an analysis of Art. 49 of the Slovenian Act on Remedies in Public Procurements Procedures. The issue of extent of damages is also discussed. The traditional view - according to which only the cost of bid preparation (so called negative interest) may be recovered - is being challenged. Under certain conditions, damages may include lost profit (so-called positive interest). Attention is called to the fact that in the sphere of application of the "utilities" directive, the cost of preparing a bid may be recovered under special (milder) conditions. In the advocated opinion, this should apply generally, to all public procurement procedures.
Keywords: izgubljeni dobiček; javno naročanje; liability of the state for damage; lost profit; negative interest; negativni pogodbeni interesi; odškodninska odgovornost države; odškodninsko pravo; povrnitev škode; public procurement; recovery of damage